A minimally invasive adjustable‐depth blunt injector for delivery of pharmaceuticals into the posterior pole. Issue 3 (25th October 2016) - Rotenstreich, Ygal; Tzameret, Adi; Kalish, Sapir E.; Bubis, Ettel; Belkin, Michael; Moroz, Iris; Rosner, Mordechai; Levy, Itay; Margel, Shlomo; Sher, Ifat
Abstract: Purpose: To investigate the feasibility and safety of a novel minimally invasive adjustable‐depth blunt injector for pharmaceuticals delivery into the posterior segment. Methods: Indocyanine green (ICG), sodium fluorescein and iron oxide nanoparticles (IONPs) were injected using the new injector into the extravascular spaces of the choroid (EVSC) compartment of rabbits and cadaver pig eyes. Spectral domain optical coherence tomography (SD‐OCT), fundus imaging and histology analysis were performed for assessment of injection safety and efficacy. Results: Indocyanine green, fluorescein and IONPs were detected across the EVSC in rabbit eyes, covering over 80 per cent of the posterior eye surface. Injected IONPs were retained in the EVSC for at least 2 weeks following injection. No retinal detachment, choroidal haemorrhage or inflammation was detected in any of the injected eyes. In cadaver pig eyes, ICG was detected across the EVSC. Conclusions: This novel minimally invasive delivery system may be used to safely deliver large volumes of pharmaceuticals into a new treatment reservoir compartment – the EVSC which can serve as a depot, in close proximity to the retina, covering most of the surface of the back of the eye without insertion of surgical instruments under the central retina. This system is predicted to enhance the therapeutic effect of treatments for posterior eye disorders.